Pengaruh Tanaman Lidah Mertua (Sansevieria Sp) Sebagai Biofilter terhadap Gambaran Histopatologi Trakea Pada Tikus Putih Jantan (Rattus Novergicus) Galur Sprague Dawley yang Diberi Paparan Asap Rokok - Nabil Abdurrahman; Rizki Hanriko; Rodiani (MAJORITY, 2021)
Smoking is a lifestyle that is currently one of the causes of health problems. Every year the number of smokers has increased. Airway irritation by cigarette smoke and other toxic substances will cause an airway inflammatory reaction. Various ways to avoid cigarette smoke bad effect have been tried, one of them is by placing the tongue-in-law (Sansevieria sp) in the room that can absorb air pollution, especially cigarette smoke. The purpose of this study was to determine the effect of tongue-in-law (Sansevieria sp) as a biofilter on tracheal cell damage in Sprague Dawley rats. The method used in this study is a randomized controlled design with a Post Test Only Control Group Desig. This research was conducted by using randomly selected samples and divided into 3 treatment groups with each group consisting of 6 white rats. In group 1 was negative control, rats were given food and drink as usual and were not exposed to cigarette smoke. In group 2 was a positive control, rats were exposed to cigarette smoke as much as 2 cigarettes per day. In group 3 is a treatment group with rats exposed to cigarette smoke and placed the tongue-in-law plant in the cage as a biofilter for 14 days. In this study was found that there were significant difference in the positive control group (who were exposed to cigarette smoke every day as much as 2 cigarettes for 14 days without the biofilter of the tongue-in-law plant) and the treatment group (with Sanseviera sp). So that it can be concluded that there was an effect of the tongue-in-law (Sansevieria sp) as a biofilter on tracheal cell damage in Sprague Dawley rats.